CREATING TEACHER’S INNOVATIVE WORK BEHAVIOR THROUGH GLOBAL LEADERSHIP AND KNOWLEDGE MANAGEMENT - Rahmawati, Ima; Permana, Johar (EARR (Educational Administration Research and Review), 2022)
The purpose of this study is to describe efforts to create innovative work behavior of teachers through global leadership and the application of knowledge management in a boarding Private High School in Bogor Regency. In this study is using a descriptive qualitative approach. Data collection techniques: interviews; observation; and documentation study. Data analysis in this study uses data reduction, data presentation and verification or conclusions. The results showed that in creating innovative work behavior, it needed a leader who was adaptive to the times, had cross-cultural and country abilities and skills in managing technology. With these skills, global leaders are able to apply knowledge management as an effort to create innovative work behavior of teachers in schools.